THE EFFECT OF USING CARD-BASED MEMORY GAMES ON VOCABULARY MASTERY OF THE SEVENTH GRADE STUDENTS AT SMP NEGERI 8 PEMATANG SIANTAR - Agustina, Aulia; Manihuruk, Leonita Maria Efipanias; Situmeang, Siska (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The aim of this research is to determine the significant impact of memory games using modified cue cards on seventh grade students' vocabulary mastery at SMP Negeri 8 Pematangsiantar in the 2024/2025 academic year. This study specifically focuses on noun mastery. This research involved a population of 320 seventh grade students, who were then selected in two classes using purposive sampling techniques. The sample consisted of an experimental class (VII-1) with 32 students involved in memory games, and a control class (VII-2) with 32 students who received traditional instruction through teacher explanations. Data collection was carried out through multiple choice pre-test and post-test. The results showed that the average score of the experimental class increased from 47.9 in the pre-test to 74.5 in the post-test. In contrast, the average score of the control class increased from 55.6 in the pre-test to 65.3 in the post-test. The analysis shows a t-test value of 4.828 with degrees of freedom calculated as (n1 + n2 - 2), resulting in a total of 62. The critical t-value at the 0.05 significance level is 1.670. Because the observed t-test value (4.828) exceeds the critical t-value (1.670), the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. These findings indicate that there is a significant influence on students' vocabulary mastery when taught using memory games with cards at SMP Negeri 8 Pematangsiantar.